A New Perspective on the Access Process - Bergenholtz, Henning; Gouws, Rufus (HERMES - Journal of Language and Communication in Business, 2010)
Only 10 or 15 years ago, you had to spend hours, days or even weeks in libraries to ﬁnd data of many kinds. Today, one has access to data at your desks at home. Therefore, the biggest problem for a real information society is not that you do not have access to the needed data, but that you cannot ﬁnd it or that it takes so long to ﬁnd it that you quit the search before ﬁnding the result. This is clearly shown by a Google search where you get so many results that can lead to a case of information stress or even worse information death. An easy search route and a short search time are important elements when trying to satisfy certain information needs. This topic is discussed based on two case studies: one concerning certain ﬁxed expressions in seven Danish printed and electronic dictionaries and one concerning looking at different access attempts in six Afrikaans reference sources, including linguistic text books, books presenting the formal spelling and orthographic rules of Afrikaans as well as a monolingual dictionary. The paper argues that the applicability of the access process, as developed in lexicography, goes beyond dictionaries, illustrating the importance of a process not relevant within the ﬁeld of linguistics but extremely important in the successful use of reference works.